EFEK SUB LETHAL AMONIA AMBIEN TERHADAP HISTOPATOLOGIS IKAN NILA (Oreochromis niloticus) YANG DIPELIHARA DALAM SISTEM BIOFLOK - Sumoharjo, Sumoharjo; Sulistyawati, Sulistyawati (Jurnal Akuakultur Rawa Indonesia, 2020)
The purpose of this research were to measure the increasing of unionized ammonia during start-up period of biofloc system for growing Nile Tilapia and to figure out its effect on histopathological changes. There was only one treatment that designed with three replication, which was 40 liters of water that contained eight fishes of each weighed 22.. The biofloc system was treated with C/N ration 12:1. Total Ammonia Nitrogen, pH and temperature were measured daily as long as 14 days. the tissue of gill, liver and kidney were cut off at the end of the experiment for histopathological examination. The result of the experiment showed that the peak of unionized ammonia concentration achieved 0.34±0.05 mg/l at 10th day. Then, decreased rapidly to 0.003±0.0009 mg/l at 14th day. The gill, liver, and kidney had regressive changes as physiologic sub lethal response of unionized ammonia expose. Keywords : Biofloc, unionized ammonia, Nile Tilapia, histopatholocal